Certain Considerations Regarding the Attributions of the Romanian Guardianship Court in the Protection of the Minors - Creț, Daniela Cristina (Journal of Legal Studies, 2020)
The minors’ vulnerability led to the adoption of certain special means of protection. Among them, special protection measures and adoption play a special role. This paper analyses the Romanian court attributions, as guardianship court in the matter of these measures which are regulated by the dispositions of the Law no. 272/2004 republished, regarding the protection and promotion of children's rights and of the Law no. 273/2004 on the procedure of adoption, and it is intended to continue the paper on the same topic from the previous issue.